Analysis of The Influence of Technology Perceived Credibility, Application Perceived Usefulness and Attitude Toward Digital Payment on Intention to Use Digital Wallet Shopee Pay - Zein, Afrizal; Amsal Nasution, Muhammad; Jansen Sinlae, Alfry Aristo; Siwi Anggraeni, Gita; Nuraini, Rini (Jurnal Informasi dan Teknologi, 2024)
The purpose of this study is to examine how consumers of e-wallets' attitudes regarding mobile payments, perceived utility, perceived ease of use, perceived credibility, and perceived self-efficacy affect their intention to utilize mobile payment behavior. This study employs a cross-sectional design and descriptive research methodology. This study combined a judicial sampling strategy with a non-probability sampling method. There were one hundred responders in this study. A questionnaire was used to obtain the data. Descriptive analysis was employed in this study to categorize respondents' responses. The structural equation model method will be used to examine the data in this study. Perceived utility and perceived simplicity of use in the context of e-wallets strongly influence attitudes toward mobile payments, according to the data processing and analysis results. In addition, the intention to use mobile payments is significantly positively influenced by one's attitude about mobile payments. Perceived self-efficacy and perceived credibility, however, do not significantly affect the intention to use mobile payments. This means that although users may feel confident in their ability to use e-wallets or believe in the reliability of e-wallets, this does not directly influence their desire to use the service. Therefore, companies do not need to focus too much on improving these two aspects to increase digital payment intention.